2013
DOI: 10.1590/s1516-18462013000400006
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da satisfação do usuário de aparelho de amplificação sonora

Abstract: OBJETIVO: avaliar a satisfação do usuário de AAS (Aparelho de Amplificação Sonora) por meio da aplicação do questionário de autoavaliação IOI-HA (International Outcome Inventory For Hearing Aids) e correlacioná-lo às características dos indivíduos, da perda auditiva e do processo de adaptação do AAS. MÉTODO: foram avaliados 98 indivíduos, de ambos os gêneros, com perda auditiva neurossensorial, de um serviço público e usuários sistemáticos de AAS há, pelo menos, três meses. O questionário IOI-HA foi aplicado, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 19 publications
2
12
0
5
Order By: Relevance
“…Because of the particular characteristics of participants' hearing loss, the hearing aids were adapted bilaterally for 38 (90.5%) of them. In all subjects, behind-the-ear (BTE) models were used: 40 (95.2%) with an earmold and two (4.8%) with open-fit HAs; these data are comparable to those described in the literature (6,7) .…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Because of the particular characteristics of participants' hearing loss, the hearing aids were adapted bilaterally for 38 (90.5%) of them. In all subjects, behind-the-ear (BTE) models were used: 40 (95.2%) with an earmold and two (4.8%) with open-fit HAs; these data are comparable to those described in the literature (6,7) .…”
Section: Discussionmentioning
confidence: 91%
“…In addition, BTEs are the preferred choice over other models because they are delivered sooner than in-ear devices. Other studies have also reported a preference for use of BTEs, and their samples were predominantly composed of elderly patients, assisted at public or private hearing clinics (6,7) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher amount of behind-the-ear (BTE) hearing aids with ear molds can be explained by the prevalent elderly age range, once the BTE model is easier to handle (24) . In the current study, only 5.43% were in-the-canal (ITC) fittings, data also found in another study, which reports only one patient using this hearing-aid model (24) . It is important to evaluate handling conditions, in order to avoid misuse and probable damages, and also facilitate users' autonomy for insertion and cleaning of their hearing aids.…”
Section: Discussionmentioning
confidence: 99%
“…Other commonly reported complaints in literature are related to the use of the telephone and discomfort with background noises (10,11,21,23,24,26) . Those complaints were evidenced in the current research: discomfort with background noises (14%), and the benefit of using the telephone (5%).…”
Section: Discussionmentioning
confidence: 99%